Determinants of Motorcycle Taxpayer Compliance: Evidence from a Border Region in Eastern Indonesia - Margareta Diana Pangastuti; Yuliati Sengkoen (Goodwood Publishing, 2026)
Purpose: This study aims to examine the effects of the tax amnesty program, income, moral obligation, and access to tax services on motorcycle taxpayer compliance in Timor Tengah Utara (TTU) Regency, a border region with relatively low tax compliance. Research Methodology: A quantitative approach was employed using a survey method. The study involved 100 respondents selected through the Slovin formula. Primary data were collected via structured questionnaires and analyzed using multiple linear regression. Results: The findings show that, simultaneously, the four variables significantly influence taxpayer compliance. Partially, the tax amnesty program, income, and moral obligation have a positive and significant effect, while tax access has a negative and significant effect on compliance. Conclusions: Taxpayer compliance in TTU Regency is influenced not only by economic capacity but also by moral awareness and accessibility to tax services. Policies that optimize tax amnesty programs, expand digital-based tax services, and strengthen moral and social education grounded in local culture can enhance voluntary tax compliance. Limitations: The study is limited to motorcycle taxpayers in TTU Regency and uses cross-sectional survey data, which may not capture changes in behavior over time. Contribution: This study contributes to the understanding of tax compliance behavior in border regions, offering practical insights for local governments and policymakers to improve regional revenue collection through culturally sensitive and accessible tax policies.